Geometric uncertainties in finite element models of mistuned bladed disks. Issue 1 (October 2016) - Koebelé‐Cousquer, Maxime; Proppe, Carsten
Abstract: This paper presents a method to develop reduced‐order models of bladed disks with geometric mistuning, which is based on polynomial choas approximation of modes of random eigenvalue subproblems. This method allows to reduce mass and stiffness matrices without evaluating the deviation in these matrices due to mistuning. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)